Optimization of an EMU train carbody by the value of the natural bending frequency - R. V. Guchinsky (Вестник Научно-исследовательского института железнодорожного транспорта, 2021)
Finding ways to optimize the body structure is an important point in the design of new electric train cars. Reducing the mass of the body leads to a lightening of the parts of the rolling stock associated with it, a reduction in energy consumption for operation and a decrease in wear in the “wheel — rail”system. Reducing the weight of the body is possible by assigning optimal rigidity to its main load-bearing elements. Increasing the rigidity of the body with a constant mass is also an important task to obtain the standard dynamic properties of the car body.The article presents method for optimizing the body structure based on calculating the value of its first frequency of natural bending vibrations. The calculation was carried out by the finite element method using a simplified beam-shell parametric model. Within the optimization calculations, 3125 working versions of sections of the main load-bearing structural elements with different rigidity were considered — bracing and cross-beams of the frame, inter-window racks and cross-beams of the roof. The sensitivity of the value of the natural vibration frequency to the change in the rigidity of the main bearing elements without taking into account the change in mass is analyzed. It was found that the rigidity of the frame bracing and cross beams has the greatest influence on the frequency value. It is shown that the ratio of the rigidity of the main bearing elements does not remain constant for optimal design options and depends on the design of the body, the target values of its mass and rigidity. When mass is limited, it is possible to choose designs that are characterized by the greatest overall body rigidity and are the most optimal in terms of manufacturability. By limiting the values of natural vibration frequency, it is possible to choose a body structure with the lowest metal mass. The presented approach allows making decisions on body modification based on the required parameters of mass and (or) the frequency of natural bending vibrations. This approach can be used in pre-design studies of the bodies of new passenger rolling stock.